Evaluation of ultrasound assisted peripheral nerve stimulator guided versus peripheral nerve stimulator guided lumbosacral plexus block for postoperative analgesia in patients undergoing lower limb surgery - Chatrath, Veena; Attri, Joginder P.; Bala, Anju; Gupta, Alisha; Gupta, Malika (International Journal of Research in Medical Sciences, 2024)
Background: The aim of the present study was to compare the efficacy of ultrasound (USG) assisted peripheral nerve stimulator (PNS) guided versus peripheral nerve stimulator (PNS) guided techniques of lumbosacral plexus block (LSPB) for postoperative analgesia. Methods: This prospective, randomized, double-blind study was conducted on 60 ASA grade I-II patients of either sex, aged 20-60 years, undergoing unilateral lower limb surgery under spinal anaesthesia. On completion of surgery, group U (30 patients) received LSPB using USG assisted PNS guided technique and group P (30 patients) received LSPB using PNS guided technique, with 0.25% injection levobupivacaine (20 ml) + injection dexamethasone (4 mg) in lumbar plexus block and 0.25% injection levobupivacaine (20 ml) + injection dexamethasone (4 mg) in sacral plexus block. Results: The mean procedure time of group U was significantly more (15.30±1.98 minutes) than that of group P (11.05±2.13 minutes) (p=0.001). The mean duration of postoperative analgesia was longer in group U (18.00±5.65 hours) as compared to group P (15.80±6.11 hours) (p>0.05). The mean number of doses of rescue analgesia with injection fentanyl in group U was 0.806±0.66 and in group P was 1.066±0.63 (p>0.05). Conclusions: USG assisted PNS guided LSPB is a better choice as compared to PNS guided technique.